Guidelines for the career development of teachers under the Special Training Division, Border Patrol Police Headquarters: แนวทางการพัฒนาความก้าวหน้าทางอาชีพของอาจารย์ในสังกัด กองบังคับการฝึกพิเศษ กองบัญชาการตำรวจตระเวนชายแดน. - chairhit1, thaimanee (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2020)
The research aims to study problems and obstacles. Analyze factors that support professional progress and To propose guidelines for the development of professional progress of teachers under the Special Training Division, Border Patrol Police Headquarters Qualitative Research In-depth Interview (15 people involved, which have analyzed in descriptive data, found that problems and obstacles to career advancement found that personnel are frequently transferred. Lack of new generation of professors Lack of motivation to work Lack of knowledge and modern teaching Shortage of teaching and learning materials Duration of work The health of the practitioner is a teacher. Multi-duty And adaptation to keep up with social changes. For the supporting factors, it is found that the structure adjustment of the job position continuously goes up Giving serious attention to the development of subordinates Providing positions and compensation for increasing knowledge and competency by providing training both domestically and internationally and the development of the operational ideology of teachers. And the way to develop career advancement, it is found that the career development of the personnel must be involved in driving the regulations and the administrative structure of the department that will result in the need to the organization to reform the structure to be Truly meets the needs Providing training and teaching Providing new experiences to keep up with current world situations Developing skills in technology and foreign languages ​​and regularly reviewing and developing oneself